Disturbance is the principal α-scale filter determining niche differentiation, coexistence and biodiversity in an alpine community - PIERCE, SIMON; LUZZARO, ALESSANDRA; CACCIANIGA, MARCO; CERIANI, ROBERTA M; CERABOLINI, BRUNO (The Journal of ecology, 2007)
1 Many current biodiversity theories assume that resource competition determines niche segregation and thus coexistence within communities (i.e. at the α-scale). However, the action of disturbance, creating heterogeneous environments and suppressing potential dominants, may also be important for biodiversity maintenance. 2 Hypothesis: subordinate species exhibit primarily opportunistic (ruderal) survival strategies, with increasing disturbance intensity constraining dominant species - favouring opportunistic strategies and thus functional and species diversity. 3 The diversity, character and frequency of strategies in an alpine sedge-dominated vascular plant community were quantified in situ using CSR (competitor, stress-tolerator, ruderal) classification, and compared with a pasture in the same alpine vegetation belt (i.e. with additional disturbance). Adaptive trends were confirmed by independent multivariate analysis [detrended correspondence analysis (DCA) and non-metric multidimensional scaling (NMDS)]. 4 The extremely stress-tolerant sedge Carex curvula (C : S : R = 17.2 : 72.9 : 9.9%) dominated the relatively undisturbed community (frequency = 52%), with 32 subordinates (typically < 5%) exhibiting a functional spectrum encompassing stress tolerance to ruderalism, but not competitive strategies. With grazing, the community exhibited weaker co-dominance by five species, greater biodiversity (76 species) and greater functional diversity, characterized by larger numbers of ruderals and some competitive-ruderals. The principal variation in both DCA1 and NMDS1 for both communities directly reflected CSR strategy spectra, confirmed by Spearman's correlation. 5 Dominance by stress-tolerators and restricted functional diversity demonstrates habitat-level (β-scale) functional convergence in response to stress. A spectrum of S to R strategies demonstrates α-scale functional divergence in response to differential stress and disturbance. Grazing suppresses potentially dominant species and favours diversity, with the additional presence of competitive-ruderals suggestive of a more intricate niche topology including more relaxed abiotic opportunities. 6 Natural communities are not necessarily structured according to the rules of resource competition models, as these fail to account for disturbance and facilitation processes.